Gratitude and academic engagement: exploring the mediating effects of internal locus of control and subjective well-being - Cui, Hongbo; Bi, Xiaoyan; Chen, Weiyu; Gao, Tao; Qing, Zaihua; Shi, Keke; Ma, Yankun (Frontiers in Psychology, 2023)
Abstract：This study aimed to explore the relationship between gratitude and academic engagement in Chinese students. The students of some junior high schools in Guangzhou were surveyed using the Gratitude Questionnaire-6, the School Engagement Questionnaire, the Levenson's IPC Scale, and the General Well-being Schedule. A total of 708 valid responses were collected. The results indicate a significant positive relationship between gratitude and academic engagement.Subjective well-being plays a mediating role between gratitude and academic engagement. Locus of control and subjective well-being serve as serial mediators between gratitude and academic engagement. These findings suggest that promoting students' academic engagement can be achieved by fostering gratitude and improving their internal locus of control and subjective well-being. By cultivating gratitude and enhancing these factors, educators and policymakers can create a more engaging and supportive learning environment for students.